Distribution of Methylomonas methanica and Methylosinus trichosporium in Cleveland Harbor as Determined by an Indirect Fluorescent Antibody-Membrane Filter Technique - Reed, William M. (1978)
An indirect fluorescent antibody-membrane filter staining technique, which permitted the autecological study of Methylomonas methanica and Methylosinus trichosporium, was developed. This technique was used to assay the numbers of these two organisms in Cleveland Harbor. The concentrations of M. methanica and M. trichosporium were found to be inversely proportional to the sampling depth, with the highest cell counts observed in the sediments. M. methanica was observed at every sampling station, whereas M. trichosporium was found at only two of the stations.